Sleep quality and associated factors among elderly in Hospital Universiti Sains Malaysia (USM) - Azman, Norakhmal Syahirah (2020)
Sleep quality among elderly during hospitalization is neglected because many think it is an only normal condition when increasing in age. This neglect is evident when many elderly complaints they having difficulty in sleep during hospitalization as well as at home. The aim of this study was to assess the sleep quality and associated factors among the elderly in Hospital USM. A cross-sectional study was undertaken involving 60 participants using purposive sampling. The questionnaire using interview face to face was used for data collection from February 2020 until March 2020. Mann-Whitney and Kruskal Wallis test was used to examine the mean score differences between selected socio-demographic factors and sleep quality during hospitalization. The mean age of the participants was 68.4 (7.4) years between 60-89 years. The findings revealed that the majority 81.7% had poor sleep quality among elderly during hospitalization. A statistically significant mean score differences were observed between sleep pattern and sleep quality in aspects number of awakenings (p = 0.02) and sleep latency (p = 0.03). Therefore, it can be concluded that the sleep quality of elderly during hospitalization was poor. Factors that associated need to be identified so that the suitable education to get better and quality sleep can be given.